Nyman_etal_to_DRYAD - Nyman, Tommi; Valtonen, Mia; Aspi, Jouni; Ruokonen, Minna; Kunnasranta, Mervi; Palo, Jukka U. (Dryad Digital Repository, 2014)
Text-formatted DIYABC data file containing microsatellite genotypes and mitochondrial control-region sequences of Saimaa, Ladoga, and Baltic ringed seals.